Influence of Digital Ecosystems on Value Creation and Competitive Positioning in the E-Commerce Industry - Orji, Geoffrey (European Journal of Business and Strategic Management, 2025)
Purpose: This study sought to investigate the influence of digital ecosystems on value creation and competitive positioning in the e-commerce industry. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to influence of digital ecosystems. Preliminary empirical review revealed that digital ecosystems significantly shaped value creation and competitive positioning in the e-commerce industry by enabling integration, innovation, and collaboration across platforms. Firms embedded in robust ecosystems adapted faster, leveraged technology more effectively, and gained sustainable competitive advantages across diverse global regions. Unique Contribution to Theory, Practice and Policy: The study recommended that businesses enhance digital ecosystem engagement through partnerships, modular strategies, and talent development, while policymakers were urged to create inclusive and supportive digital infrastructure and governance frameworks to foster competitiveness and innovation in e-commerce.